On the origin of the village name Jaunódava - Bilkis, Laimutis (Baltistica, 2019)
The paper analyses the evolution and origin of Jaunódava, the name of a village located in the Kaltinėnai civil parish of the Šilalė region. It is argued that the current modern language form is secondary and, due to folk etymology, emerged from *Jonaudai → *Jonaudava, which was derived from the Lithuanian compound anthroponym Jó-naudas. This theory is based on the following name entries in historical sources: Jonawdo (German), Janowdowo, Яновдовo, Janowdowa, Jonowdow, Janowdów, Яновдовь, Janowdow.
Keywords: Lithuanian; historical toponymy; origin of oikonyms; evolution of oikonyms; folk etymology